Integration of technologies policies and Basic Education Teacher Training in Uruguay - Rosana Elizabeth Martínez Barcellos; Carlinda Leite; Angélica María Reis Monteiro (Arizona State University, 2016)
This article takes into discussion as problematic Initial Teacher Training (ITT) of Basic Education in Uruguay and analyses the place of information and communication technologies (ICT) in it, and also how they are influenced (Ball, 1998, 2001; Bowe, Ball Gold, 1992) by international policies and how they are recontextualized (Bernstein, 1993, 1998). The questions that guide the study are: What did the Global Agenda on ICT stated in the ITT? What influences do these policies have on ITT? How recontextualization process occurs? In the empirical part, the study collected and analyzed ITT plans and interviews with the director of the course, training teachers and students who are doing their teaching practice. These data, processed by content analysis, suggests that there is a global agenda that points to the need of ICT integration in education, and as a result, initial teacher training should have content that ensures the effective use ICT. This global agenda influences Uruguay's education policies which are recontextualized through institutional practices that have to adapt to students and teacher's needs. Nevertheless, at teacher training level, an investment is needed in order to achieve the objectives towards policies that aim at ICT integration.